Pengembangan Media Pembelajaran Pada Mata Kuliah Ketel Uap Berbasis Engine Simulator di Program Studi Tekni - Saktiono, Maxima Ari (Universitas Hang Tuah, 2020)
Teaching and learning process is the core of the overall education process with the teacher as the main role holder. Many teaching and learning events are rooted in various views and concepts. Therefore the embodiment of the teaching and learning process can occur in various models. Teaching and learning process is a process of mutual interaction between instructors and students in educational situations to achieve certain goals. Learning methods carried out so far are still mostly done with theoretical teaching methods in class. The Ship Machinery Study Program has an Engine Simulator Laboratory that can be used as a learning medium for cadets, one of which is the Steam Boil course. To find out the level of understanding of the subject of the Steam boiler with theoretical learning methods in class with learning methods using the Engine Simulator, the Cadets were given a questionnaire containing the level of understanding with the 2 methods. From the results of the questionnaire obtained data, then the data is processed using statistical software. The data was tested using 2 methods namely the Normality Test and the T Test. Based on the results of the Kolmogorov-Smirnov Normality Test, values obtained before and after being treated were 0.053 and 0.20 because these values were greater than 0.05, so the data were normally distributed. While based on the T Test, the Sig (2-tailed) value is 0,000 < 0.05, so the decision that can be taken is to reject H0 or accept H1. So it can be concluded that there are significant differences in value before being treated using the Engine Simulator and after being treated using the Engine Simulator.